The Social Functions of Rumah Gadang of Kinari Village in Modern Society - Jingling, Zhang (International Journal of Culture and Art Studies, 2021)
Rumah Gadang is a traditional house for Minangkabau people, the majority of whom live in West Sumatra. In addition to being a place of residence for the matrilineal family, the traditional house and a place of family consultation, places of ceremonies, inheritance of custom values, and representations of matrilineal culture. The paper will analyze the change of the traditional house function and its factors based on 146 traditional Nagari Kinari. The study uses a qualitative approach to identifying and collecting field data through the fieldwork in Nagari Kinari, Solok. The result shows that traditional houses in Kinari have dramatically changed their functions in matrilineal families' homes and educational centres. However, they are still places for important ceremonies and the manifestation of social status. The function in essential ceremonies and social status symbols These changes occur due to social changes, including changes in family structure, economic income, the national education system and personal awareness, and differences in understanding traditional culture.